Members of a supply chain and their relationships - Ványi , Noémi (Applied Studies in Agribusiness and Commerce, 2012)
Today, companies do not compete individually on the market, but as members of a supply chain, delivering their goods or services to customers through shared collaboration. The main objective of the members in the chain is to satisfy customer needs, in the interest of which they cooperate in value adding processes. The main objective of the present study is to characterise the members of a supply chain, their relationship and to measure performance. The most relevant literature published on this topic states that investigation of the performance measurement in supply chains from the side of relationships is considered ‘uncharted territory’. However, the operation of a supply chain cannot be described without investigating its relationships.